A REVIEW ON THE APPLICATION OF SUSTAINABLE MODERN HIVES AMONG STINGLESS BEEKEEPER IN MALAYSIA - Falex J Langkan; Viduriati Binti Sumin; Hazmi Ag Damit; Normah Awang Besar; Mohd Effendi Bin Wasli (International Journal of Accounting, Finance and Business, 2022)
Sustainable practices are one way to address the growing environmental problem. The application of Sustainable modern hives plays a significant role in Malaysia's socioeconomic development and environmental conservation. In conventional practices, the colony was obtained from the bee logs hunting activities or natural hives by cutting down trees, which disturb the natural habitat. The lack of awareness has led to designing a new phase of modern hives with sustainable characteristics to conserve the natural habitat ecosystem. These days, the alternative modern hives proved to be the solution for developing a sustainable stingless beekeeping industry in Malaysia and one of the strategies to increase the revenue in stingless beekeeping business by using multiplication of stingless bees' colony method. Thus, this study aimed to compile the transition process of hives design used by stingless beekeeping in Malaysia. Nowadays, both conventional and modern designs of hives are used locally. The review results revealed the transition from conventional to sustainable modern hives approaches used by the stingless beekeeper and comply with the standard of My GAP A.M. in stingless bee farm activity.